Crise global e a necropolítica do governo Bolsonaro em tempos de pandemia - Osmar G. Alencar (Ciências Sociais Unisinos, 2020)
This article aims to analyze the crisis of global capitalism and the response of the Brazilian State to safeguard the contradictory interests of capital and labor in times of pandemic. It is theoretically based on the conceptions of structural crisis by Poulantzas (1977) on capitalism crisis by Harvey (2011), on the global crisis by Farias (2015) as opposed to crisis of neoliberalism by Duménil and Lévy (2014); and in the political strategy for overcome crisis based on concepts of biopolitics by Foucault (2010) and necropolitics by Mbembe (2020). The economic measures taken by the Bolsonaro government to minimize the impact of Coronavirus on the routine of companies and people lives showed the darkest facet of Brazilian neoliberalism, that is, of Brazilian necroliberalism in this pandemic: the workforce that no (more) produces value will be discarded. Necroliberalism on macroeconomic policy is the practical expression of Bolsonaro government’s genocidal necropolitics in times of pandemic.